Anti-inflammatory, analgesic, and antipyretic potential of Oxystelma esculentum (L. f.) Sm. using in vitro, in vivo, and in silico studies - Sherif, Asmaa E.; Sajid-ur-Rehman, Muhammad; Asif, Muhammad; Qadeer, Iram; Khan, Kashif ur Rehman (Frontiers in Pharmacology, 2024)
The objective of the current study was to evaluate the anti-inflammatory, analgesic, and antipyretic potential of Oxystelma esculentum using different animal models. The phytochemical profile was determined by assessing its total phenolic content (TPC) and total flavonoid content (TFC), followed by the high-performance liquid chromatography (HPLC) technique. The in vitro anti-inflammatory potential of O. esculentum ethanolic extract (OEE) was evaluated by lipoxygenase enzyme inhibition activity and a human red blood cell (HRBC) membrane stability assay. The in vivo anti-inflammatory potential of the plant was determined by the carrageenan-induced paw edema test, and the analgesic potential by the hot plate test, tail-flick test, formalin-induced analgesia, acetic acid-induced writhing activities, and yeast-induced elevation of body temperature. The values of total phenolic content (212.6 ± 3.18 µg GAE/g) and total flavonoid content (37.6 ± 1.76 µg QE/g) were observed. The results showed that OEE exhibited significant antioxidant capacity in DPPH (2,2-diphenyl-1-picrylhydrazyl) (266.3 ± 7.35 μmol TE/g), ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (1,066.3 ± 7.53 μmol TE/g), and FRAP (ferric reducing antioxidant power) (483.6 ± 3.84 μmol TE/g) assays. The HPLC analysis demonstrated phytocompounds with anti-inflammatory potential, such as chlorogenic acid, gallic acid, 4-hydroxybenzoic acid, caffeic acid, ferulic acid, and coumarin. The plant showed in vitro anti-inflammatory activity through the inhibition of lipoxygenase enzyme with a high percentage (56.66%) and HRBC membrane stability (67.29%). In in vivo studies, OEE exhibited significant (p < 0.05) anti-inflammatory (carrageenan-induced paw edema model), analgesic (hot plate test, tail-flick test, formalin-induced analgesia, and acetic acid-induced writhing), and antipyretic (rectal temperature reduction) responses at different doses (100, 300, and 500 mg/kg). Molecular docking studies showed significant binding affinities of phytocompounds compared to indomethacin and predicted various binding interactions for stable conformations. The results of in vitro, in vivo, and in silico studies supported the anti-inflammatory, analgesic, and antipyretic potential of O. esculentum.